The Occurrence of Cheyne–Stokes Respiration in Congestive Heart Failure: The Effect of Age - Pe'Er, Avivit; Lorber, Avraham; Suraiya, Suheir; Malhotra, Atul; Pillar, Giora (Frontiers in Psychiatry, 2010)
Introduction: Up to 50% of adults with congestive heart failure (CHF) and left ventricular dysfunction demonstrate Cheyne Stokes Respiration (CSR), although the mechanisms remain controversial. Because CSR has been minimally studied in children, we sought to assess the prevalence of CSR in children with low and high output cardiac failure. We hypothesized that the existence of CSR only in children with low output CHF would support the importance of circulatory delay as a CSR mechanism. Methods: Thirty patients participated: 10 children with CHF, 10 matched children with no heart disease, and 10 adults with CHF. All participants underwent an in-laboratory polysomnographic sleep study. Results: CHF Children’s average age (±SEM) was 3.6±2.1 years vs. 3.7±2 years in the age-matched control group. The average ejection fraction of three children with low-output CHF was 22±6.8%. The remaining seven had normal-high cardiac output. Compared to control children, CHF children were tachypneic and tachycardic during stable sleep (55.1±6.7 vs. 26.9±3 breath/min and 127.6±8.7 vs. 97.6±6.9 beats/min, respectively, p<0.05 for both). They had shorter total sleep time (195±49 vs. 373±16 min, p<0.05) with a low sleep efficiency of 65.6±6%. None of the children had a pattern of CSR at any time during the studies while the adults with CHF had 40% prevalence of CSR. Conclusions: The complete absence of CSR in our sample of children with CHF compared to the 40% prevalence in the adults with CHF we studied, suggests that CSR may be an age-dependent phenomenon. Thus, we speculate that regardless of the exact mechanism which drives CSR, age is an over-riding factor.